2021
DOI: 10.3390/su13105369
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Hazard Risk Assessment of Kathmandu Valley, Nepal

Abstract: Natural hazards are complex phenomena that can occur independently, simultaneously, or in a series as cascading events. For any particular region, numerous single hazard maps may not necessarily provide all information regarding impending hazards to the stakeholders for preparedness and planning. A multi-hazard map furnishes composite illustration of the natural hazards of varying magnitude, frequency, and spatial distribution. Thus, multi-hazard risk assessment is performed to depict the holistic natural haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 64 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…This potential reduces towards the valley edge. More recent assessments have indicated that the highest potential is at locations near the rivers and in the central valley (Gautam et al 2017), and probabilistic assessments have reported similar findings (Sajan et al 2020;Khatakho et al 2021). However, this has been attributed to the older sequences and as the Valley contains a complex mix of laminated sequences it remains a challenge to evaluate the liquefaction potential in the valley.…”
Section: Geologymentioning
confidence: 75%
“…This potential reduces towards the valley edge. More recent assessments have indicated that the highest potential is at locations near the rivers and in the central valley (Gautam et al 2017), and probabilistic assessments have reported similar findings (Sajan et al 2020;Khatakho et al 2021). However, this has been attributed to the older sequences and as the Valley contains a complex mix of laminated sequences it remains a challenge to evaluate the liquefaction potential in the valley.…”
Section: Geologymentioning
confidence: 75%
“…The fire risk index system, including the factors and weights, varies depending on the country/region and building type. Some studies have built risk index systems for the fire risk in IS [ 30 , 31 , 32 , 33 ], but the risk index systems are quite different for different IS cases, and the risk characteristics of IS are not summarized under the same evaluation system. In this research, we chose a fire risk index system developed by Global Safety Tanzer Technology Company.…”
Section: Risk Assessment Methodsmentioning
confidence: 99%
“…The geographical location of Kathmandu Valley, as shown in Fig. 1, is in central Nepal, with coordinates ranging from 85°11′34"E to 85°31′19"E longitude and 27°32′16"N to 27°48′47.75"N Latitude (Khatakho et al, 2021). The Kathmandu Valley comprises three main historical cities Kathmandu (the capital of Nepal), Lalitpur, and Bhaktapur.…”
Section: Introductionmentioning
confidence: 99%